Castable for iron-making blast furnace hearth and preparation method of castable
By using castables containing components such as titanium corundum in the blast furnace cylinder, titanium nitride is used to generate titanium nitride, which solves the problems of erosion and damage of blast furnace lining materials, extends the service life and reduces costs and energy consumption.
Patent Information
- Application Number
- CN202411795913.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
The blast furnace hearth lining material is eroded and damaged during long-term use, resulting in an increase in temperature and a decrease in safety factor. Normal addition of titanium furnaces will waste titanium resources, increasing iron smelting costs and energy consumption.
A castable material including plate-shaped corundum, titanium corundum, silicon carbide, alumina and silicon dioxide is used to carry out pumping and casting construction after stirring evenly. Titanium corundum is used to generate titanium nitride in a high-temperature environment to improve the material's high temperature resistance, wear resistance and slag iron corrosion resistance.
It significantly improves the service life of materials in the furnace cylinder, avoids the waste of titanium resources, reduces the cost of iron smelting and energy consumption, and is convenient to construct and short construction period.
Smart Images

Figure BDA0005176691120000061 
Figure BDA0005176691120000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of unshaped refractory materials, and in particular relates to a castable for an iron-making blast furnace hearth and a preparation method thereof. Background Art
[0002] The blast furnace hearth is the main iron-making equipment that performs continuous high-temperature operations. It is an important guarantee for high efficiency and low consumption of steel enterprises. The hearth is a key part for safety and longevity in the blast furnace production process. The working condition of the blast furnace hearth will directly affect the blast furnace production indicators and economic benefits, and is an important basis for maintaining the high efficiency, low consumption and longevity of the blast furnace. During blast furnace ironmaking production, the hearth is subjected to long-term physical swirl and eddy current scouring and chemical erosion by molten iron, resulting in melting loss and damage to the hearth. Therefore, taking effective measures to improve the hearth structure and material to extend the service life of the blast furnace is the work goal of the majority of ironmaking workers. At present, the overall casting construction process of the hearth has been known and accepted by most ironmaking workers. However, as the service life of the blast furnace continues to increase, the lining material of the hearth is constantly eroded and damaged, resulting in increased temperature, thereby causing a decrease in the safety factor. In severe cases, major accidents such as hearth burn-through may even occur, threatening the lives and property safety of on-site personnel. Therefore, when the hearth temperature is abnormal, ironmaking workers usually consider adding titanium to protect the furnace to control the hearth temperature. However, normalized titanium addition not only wastes titanium resources excessively, but also increases ironmaking costs and energy consumption. Summary of the invention
[0003] The purpose of the present invention is to provide a castable for the hearth of an iron-making blast furnace, which is used to replace traditional ceramic cups (plastic corundum bricks, corundum mullite bricks, etc.) or other hearth castables, and can improve the material's high temperature resistance, wear resistance, resistance to slag and iron corrosion and other properties, thereby greatly improving the material's service life in the hearth and solving the problems of wasting resources, increasing iron-making costs and energy consumption.
[0004] Another object of the present invention is to provide a method for preparing a castable for an iron-making blast furnace hearth.
[0005] The present invention adopts the following technical solution:
[0006] A castable for a furnace hearth of an iron-making blast furnace, the castable comprising the following components: 8-18 parts by weight of plate-shaped corundum 5-8mm particles, 9-19 parts by weight of plate-shaped corundum 3-5mm particles, 15-25 parts by weight of titanium corundum 1-3mm particles, 9-19 parts by weight of titanium corundum 0-1mm particles, 0-6 parts by weight of 97 silicon carbide 0-1mm particles, 6-10 parts by weight of 97 silicon carbide 100M powder, 2-12 parts by weight of 97 silicon carbide 200M powder, 1-9 parts by weight of titanium corundum 200M powder, 10-14 parts by weight of alumina micropowder, 2-6 parts by weight of 96 silicon dioxide micropowder, 0.01-0.05 parts by weight of 1 additive, 0.01-0.05 parts by weight of 2 additives, and 0.05-0.15 parts by weight of 3 additives.
[0007] Furthermore, the castable includes the following components: 11-15 parts by weight of plate-like corundum 5-8mm particles, 12-16 parts by weight of plate-like corundum 3-5mm particles, 18-22 parts by weight of titanium corundum 1-3mm particles, 12-16 parts by weight of titanium corundum 0-1mm particles, 2-4 parts by weight of 97 silicon carbide 0-1mm particles, 7-9 parts by weight of 97 silicon carbide 100M powder, 5-9 parts by weight of 97 silicon carbide 200M powder, 3-7 parts by weight of titanium corundum 200M powder, 11-13 parts by weight of alumina micropowder, 3-5 parts by weight of 96 silicon dioxide micropowder, 0.02-0.04 parts by weight of 1 additive, 0.02-0.04 parts by weight of 2 additives, and 0.07-0.12 parts by weight of 3 additives.
[0008] Furthermore, the castable is composed of the following components: 13 parts by weight of plate-like corundum 5-8mm particles, 14 parts by weight of plate-like corundum 3-5mm particles, 20 parts by weight of titanium corundum 1-3mm particles, 14 parts by weight of titanium corundum 0-1mm particles, 3 parts by weight of 97 silicon carbide 0-1mm particles, 8 parts by weight of 97 silicon carbide 100M powder, 7 parts by weight of 97 silicon carbide 200M powder, 5 parts by weight of titanium corundum 200M powder, 12 parts by weight of alumina micropowder, 4 parts by weight of 96 silicon dioxide micropowder, 0.03 parts by weight of 1 additive, 0.03 parts by weight of 2 additives, and 0.1 parts by weight of 3 additives.
[0009] Furthermore, the Al2O3 content of the titanium corundum is 55-75%, the Ti2O3 content is 20-40%, the impurity content is ≤5%, and the volume density is ≥3.85g / cm 3 .
[0010] Furthermore, the additive 1 is dispersant SP70.
[0011] Furthermore, the 2nd additive is 200M aluminum powder.
[0012] Furthermore, the 3 admixture is 200M silicon powder.
[0013] A method for preparing a castable for an ironmaking blast furnace hearth as described in any of the above items comprises the following steps: 1) adding all raw materials in the formula into a powerful mixer with a rotation speed of 20r / min in sequence, and stirring for 5 minutes; 2) taking samples for measurement after the materials are completely stirred; 3) determining the construction performance of the materials, and bagging and storing them after meeting the requirements.
[0014] The method for preparing a castable for an iron-making blast furnace hearth is as follows: when in use, a whole package of prepared materials is added into a powerful mixer with a rotation speed of 20 r / min, and 7-8% by weight of 40 silica sol is added, stirred for 5 minutes, the materials are observed, and after the materials are completely stirred and uniformly, pumping and pouring construction is carried out.
[0015] Compared with the prior art, the present invention has the following positive and beneficial effects:
[0016] 1. The blast furnace hearth castable prepared by the present invention utilizes the working principle of adding titanium to protect the furnace, that is, the low-valent titanium on the surface of the castable undergoes a nitridation reaction in the special environment of the blast furnace hearth to generate titanium nitride, and titanium nitride has a series of advantages such as high melting point, high hardness, wear resistance, resistance to slag iron erosion, resistance to slag iron infiltration, and high stability, thereby improving the castable's better high-temperature performance.
[0017] 2. The blast furnace hearth castable prepared by the present invention has a convenient and easy-to-operate construction method, and can be pumped and constructed according to a normal hearth castable construction method.
[0018] 3. The blast furnace hearth castable prepared by the present invention is time-saving and efficient during construction, has better properties of the castable, and can shorten the overall construction period.
[0019] 4. The blast furnace hearth castable prepared by the present invention has excellent performance and is more suitable for the blast furnace hearth environment than existing castables, and can greatly extend the service life of the material, thereby ensuring the service life of the blast furnace.
[0020] 5. The blast furnace hearth castable prepared by the present invention avoids a large amount of waste of titanium resources in the later stage of the blast furnace, and reduces ironmaking costs and energy consumption. DETAILED DESCRIPTION
[0021] The present invention will be further explained below in conjunction with the embodiments.
[0022] The castable for the hearth of an ironmaking blast furnace proposed in the present invention comprises the following components: 8-18 parts by weight of plate-shaped corundum 5-8 mm particles, 9-19 parts by weight of plate-shaped corundum 3-5 mm particles, 15-25 parts by weight of titanium corundum 1-3 mm particles, 9-19 parts by weight of titanium corundum 0-1 mm particles, 0-6 parts by weight of 97 silicon carbide 0-1 mm particles, 6-10 parts by weight of 97 silicon carbide 100M powder, 2-12 parts by weight of 97 silicon carbide 200M powder, and 10 parts by weight of 100M granules of 97 silicon carbide. parts by weight, titanium corundum 200M powder 1-9 parts by weight, alumina powder 10-14 parts by weight, 96 silicon dioxide powder 2-6 parts by weight, 1 additive 0.01-0.05 parts by weight, 2 additives 0.01-0.05 parts by weight, 3 additives 0.05-0.15 parts by weight, wherein the Al2O3 content of titanium corundum is 55-75%, the Ti2O3 content is 20-40%, the impurity content is ≤5%, and the volume density is ≥3.85g / cm 3 , among which 1 additive is dispersant SP70, 2 additive is 200M aluminum powder, and 3 additive is 200M silicon powder.
[0023] Example 1
[0024] Material preparation: Take 8 parts by weight of plate-like corundum 5-8mm particles, 9 parts by weight of plate-like corundum 3-5mm particles, 15 parts by weight of titanium corundum 1-3mm particles, 9 parts by weight of titanium corundum 0-1mm particles, 0 parts by weight of 97 silicon carbide 0-1mm particles, 6 parts by weight of 97 silicon carbide 100M powder, 2 parts by weight of 97 silicon carbide 200M powder, 1 part by weight of titanium corundum 200M powder, 10 parts by weight of alumina micropowder, 2 parts by weight of 96 silicon dioxide micropowder, 0.01 parts by weight of 1 additive, 0.01 parts by weight of 2 additives, and 0.05 parts by weight of 3 additives. Among them, the Al2O3 content of titanium corundum is 55%, the Ti2O3 content is 20%, the impurity content is ≤5%, and the bulk density is ≥3.85g / cm 3 , among which 1 additive is dispersant SP70, 2 additive is 200M aluminum powder, and 3 additive is 200M silicon powder.
[0025] Preparation method: Add all the raw materials in the formula into a high-powered mixer with a speed of 20r / min in sequence, and stir for 5 minutes. After the materials are completely mixed, take samples for measurement, and after confirming that the construction performance of the materials meets the requirements, bag them for storage.
[0026] Example 2
[0027] Material preparation: Take 18 parts by weight of plate-like corundum 5-8mm particles, 19 parts by weight of plate-like corundum 3-5mm particles, 25 parts by weight of titanium corundum 1-3mm particles, 19 parts by weight of titanium corundum 0-1mm particles, 6 parts by weight of 97 silicon carbide 0-1mm particles, 10 parts by weight of 97 silicon carbide 100M powder, 12 parts by weight of 97 silicon carbide 200M powder, 9 parts by weight of titanium corundum 200M powder, 14 parts by weight of alumina micropowder, 6 parts by weight of 96 silicon dioxide micropowder, 0.05 parts by weight of 1 additive, 0.05 parts by weight of 2 additives, and 0.15 parts by weight of 3 additives. Among them, the Al2O3 content of titanium corundum is 75%, the Ti2O3 content is 40%, the impurity content is ≤5%, and the bulk density is ≥3.85g / cm 3 , among which 1 additive is dispersant SP70, 2 additive is 200M aluminum powder, and 3 additive is 200M silicon powder.
[0028] The preparation method is: add all the raw materials in the formula into a high-powered mixer with a rotation speed of 20r / min in sequence, stir for 5 minutes, and after the materials are completely stirred, take samples for measurement, and after confirming that the construction performance of the materials meets the requirements, bag them for storage.
[0029] Example 3
[0030] Material preparation: Take 13 parts by weight of plate-like corundum 5-8mm particles, 14 parts by weight of plate-like corundum 3-5mm particles, 20 parts by weight of titanium corundum 1-3mm particles, 14 parts by weight of titanium corundum 0-1mm particles, 3 parts by weight of 97 silicon carbide 0-1mm particles, 8 parts by weight of 97 silicon carbide 100M powder, 7 parts by weight of 97 silicon carbide 200M powder, 5 parts by weight of titanium corundum 200M powder, 12 parts by weight of alumina micropowder, 4 parts by weight of 96 silicon dioxide micropowder, 0.03 parts by weight of 1 additive SP70 dispersant, 0.03 parts by weight of 2 additive 200M aluminum powder, and 0.1 parts by weight of 3 additive 200M silicon powder, wherein the Al2O3 content of titanium corundum is 65%, the Ti2O3 content is 30%, the impurity content is ≤5%, and the bulk density is ≥3.85g / cm 3 .
[0031] The preparation method is: add all the raw materials in the formula into a high-powered mixer with a rotation speed of 20r / min in sequence, stir for 5 minutes, and after the materials are completely stirred, take samples for measurement, and after confirming that the construction performance of the materials meets the requirements, bag them for storage.
[0032] Example 4
[0033] Take 11 parts by weight of plate-like corundum 5-8mm particles, 12 parts by weight of plate-like corundum 3-5mm particles, 18 parts by weight of titanium corundum 1-3mm particles, 12 parts by weight of titanium corundum 0-1mm particles, 2 parts by weight of 97 silicon carbide 0-1mm particles, 7 parts by weight of 97 silicon carbide 100M powder, 5 parts by weight of 97 silicon carbide 200M powder, 3 parts by weight of titanium corundum 200M powder, 11 parts by weight of alumina micropowder, 3 parts by weight of 96 silicon dioxide micropowder, 0.02 parts by weight of 1 additive SP70 dispersant, 0.02 parts by weight of 2 additive 200M aluminum powder, and 0.07 parts by weight of 3 additive 200M silicon powder. The selected titanium corundum has an Al2O3 content of 55-75%, a Ti2O3 content of 20-40%, an impurity content of ≤5%, and a bulk density of ≥3.85g / cm 3 , add all the raw materials in the formula into a high-powered mixer with a speed of 20r / min in turn, stir for 5 minutes, and after the materials are completely mixed, take samples for measurement, and after confirming that the construction performance of the materials meets the requirements, bag them for storage.
[0034] Example 5
[0035] Take 15 parts by weight of plate-like corundum 5-8mm particles, 16 parts by weight of plate-like corundum 3-5mm particles, 22 parts by weight of titanium corundum 1-3mm particles, 16 parts by weight of titanium corundum 0-1mm particles, 4 parts by weight of 97 silicon carbide 0-1mm particles, 9 parts by weight of 97 silicon carbide 100M powder, 9 parts by weight of 97 silicon carbide 200M powder, 7 parts by weight of titanium corundum 200M powder, 13 parts by weight of alumina powder, 5 parts by weight of 96 silicon dioxide powder, 0.04 parts by weight of 1 additive SP70 dispersant, 0.04 parts by weight of 2 additive 200M aluminum powder, and 0.12 parts by weight of 3 additive 200M silicon powder. The selected titanium corundum has an Al2O3 content of 55-75%, a Ti2O3 content of 20-40%, an impurity content of ≤5%, and a bulk density of ≥3.85g / cm 3 , add all the raw materials in the formula into a high-powered mixer with a speed of 20r / min in turn, stir for 5 minutes, and after the materials are completely mixed, take samples for measurement, and after confirming that the construction performance of the materials meets the requirements, bag them for storage.
[0036] When using the castable prepared in Example 1-5: add the whole package of prepared material into a powerful mixer with a speed of 20r / min, add 7-8% by weight of 40 silica sol, stir for 5 minutes, observe the material, and after the material is completely stirred and uniform, pump and cast it.
[0037] The following is a detailed description of this material from the perspective of the characteristics of a certain raw material contained in the formula:
[0038] (1) This material contains titanium corundum particles and fine powder. The specially purchased titanium corundum itself is composed of Al2O3 and Ti2O3, and Ti2O3 undergoes nitridation reaction to generate TiN under the internal environment of the blast furnace. Therefore, it has a series of advantages such as high melting point, high hardness, wear resistance, resistance to slag iron erosion, resistance to slag iron infiltration, and high stability, thus giving the castable better high-temperature performance;
[0039] (2) This material contains plate-shaped corundum particles and fine powder. Due to its high-purity and low-melting-point phase, it has high high-temperature performance and stability, which further supports the service life of the material under extremely harsh conditions such as the furnace hearth;
[0040] (3) Silicon carbide is added to this material to increase the thermal conductivity and wear resistance of the material. Since the blast furnace hearth is equipped with cooling walls, increasing the thermal conductivity of the material can effectively reduce the temperature of the hot end of the material, pushing the 1150°C isotherm into the furnace, and the stagnant slag iron layer formed can effectively protect the material from scouring and erosion;
[0041] (4) Alumina powder is added to the material. As a kind of powder, it has fine particle size and plays a filling role, reduces the amount of glue added to the material, increases the density of the material, and thus improves the performance of various materials;
[0042] (5) This material contains 96 silica powder, which is a kind of powder with fine particle size. It plays a filling role, reduces the amount of glue added to the material, increases the density of the material, and thus improves the performance of various materials.
[0043] Related experiments and data
[0044] 1. Experimental purpose:
[0045] The construction performance and use performance of a castable used for the hearth of an iron-making blast furnace were compared with that of an ordinary castable, and conclusions were drawn through data analysis of the various properties of the two materials.
[0046] 2. Experimental steps:
[0047] (1) Material preparation: A castable for an ironmaking blast furnace hearth (hereinafter referred to as "CM-TA 20") and a common castable (hereinafter referred to as "CM-CS 60SX") were prepared according to a specified material preparation method.
[0048] (2) Sample preparation: In accordance with national standards, the material CM-TA 20 is prepared by casting using a 40 mm × 40 mm × 160 mm mold; the material CM-CS 60SX is prepared by casting using a 40 mm × 40 mm × 160 mm mold.
[0049] (3) Performance testing: According to the national standard, the working time and solidification time of CM-TA 20 and CM-CS 60SX were tested respectively, and the volume density, room temperature compressive strength, room temperature flexural strength, permanent linear change rate and thermal conductivity after firing at 110℃×24h, 815℃×3h and 1450℃×3h were tested respectively. The specific experimental data are shown in Table 1.
[0050] Table 1. Experimental data
[0051]
[0052]
[0053] (4) Data analysis and conclusion: As can be seen from Table 1, compared with "CM-CS 60SX", "CM-TA 20" has better performance in terms of bulk density, room temperature pressure resistance and flexural strength, permanent linear change rate and thermal conductivity, and can fully meet the specific use requirements.
Claims
1. A castable for an ironmaking blast furnace hearth, characterized in that: The castable comprises the following components: 8-18 parts by weight of plate-like corundum 5-8mm particles, 9-19 parts by weight of plate-like corundum 3-5mm particles, 15-25 parts by weight of titanium corundum 1-3mm particles, 9-19 parts by weight of titanium corundum 0-1mm particles, 0-6 parts by weight of 97 silicon carbide 0-1mm particles, 6-10 parts by weight of 97 silicon carbide 100M powder, 2-12 parts by weight of 97 silicon carbide 200M powder, 1-9 parts by weight of titanium corundum 200M powder, 10-14 parts by weight of alumina micropowder, 2-6 parts by weight of 96 silicon dioxide micropowder, 0.01-0.05 parts by weight of 1 additive, 0.01-0.05 parts by weight of 2 additives, and 0.05-0.15 parts by weight of 3 additives.
2. A castable for an ironmaking blast furnace hearth according to claim 1, characterized in that: The castable comprises the following components: 11-15 parts by weight of plate-like corundum 5-8mm particles, 12-16 parts by weight of plate-like corundum 3-5mm particles, 18-22 parts by weight of titanium corundum 1-3mm particles, 12-16 parts by weight of titanium corundum 0-1mm particles, 2-4 parts by weight of 97 silicon carbide 0-1mm particles, 7-9 parts by weight of 97 silicon carbide 100M powder, 5-9 parts by weight of 97 silicon carbide 200M powder, 3-7 parts by weight of titanium corundum 200M powder, 11-13 parts by weight of alumina micropowder, 3-5 parts by weight of 96 silicon dioxide micropowder, 0.02-0.04 parts by weight of 1 additive, 0.02-0.04 parts by weight of 2 additives, and 0.07-0.12 parts by weight of 3 additives.
3. A castable for an ironmaking blast furnace hearth according to claim 2, characterized in that: The castable is composed of the following components: 13 parts by weight of plate-like corundum 5-8mm particles, 14 parts by weight of plate-like corundum 3-5mm particles, 20 parts by weight of titanium corundum 1-3mm particles, 14 parts by weight of titanium corundum 0-1mm particles, 3 parts by weight of 97 silicon carbide 0-1mm particles, 8 parts by weight of 97 silicon carbide 100M powder, 7 parts by weight of 97 silicon carbide 200M powder, 5 parts by weight of titanium corundum 200M powder, 12 parts by weight of alumina micropowder, 4 parts by weight of 96 silicon dioxide micropowder, 0.03 parts by weight of 1 additive, 0.03 parts by weight of 2 additives, and 0.1 parts by weight of 3 additives.
4. A castable for an ironmaking blast furnace hearth according to any one of claims 1 to 3, characterized in that: The titanium corundum has an Al2O3 content of 55-75%, a Ti2O3 content of 20-40%, an impurity content of ≤5%, and a bulk density of ≥3.85 g / cm 3 .
5. A castable for an ironmaking blast furnace hearth according to any one of claims 1 to 3, characterized in that: The additive 1 is dispersant SP70.
6. A castable for an ironmaking blast furnace hearth according to any one of claims 1 to 3, characterized in that: The 2nd additive is 200M aluminum powder.
7. A castable for an ironmaking blast furnace hearth according to any one of claims 1 to 3, characterized in that: The 3 admixture is 200M silicon powder.
8. A method for preparing a hearth castable for an ironmaking blast furnace according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Add all the ingredients in the formula into a high-powered mixer at a speed of 20 r / min and stir for 5 minutes; 2) After the materials are completely mixed, take samples for measurement; 3) Determine the construction performance of the materials and bag them for storage after they meet the requirements.
9. The method for preparing a castable for an ironmaking blast furnace according to claim 8, characterized in that: When using, add the whole package of prepared materials into a high-powered mixer at a speed of 20r / min, add 7-8% by weight of 40 silica sol, stir for 5 minutes and observe the material. After the material is completely stirred, pump and pour it.
Citation Information
Patent Citations
Cement-free high-performance pumping hearth material
CN113321495A
Self-healing type wet-process spray coating for repairing ladle and spray coating method of self-healing type wet-process spray coating
CN118184305A